Preparação de carvão ativado a partir de resíduos vegetais para a adsorção de ácido 2,4 diclorofenoxiacético (2,4-D), atrazina e cetoprofeno de soluções aquosas - Salomón, Yamil Lucas de Oliveira (2024)
This study proposes the use of adsorption techniques for the removal of emerging pollutants commonly found dissolved in water and sewage, such as herbicides and pharmaceutical products. In this context, the adsorbents were prepared from activated carbon derived from plant residues, specifically the endocarp of the queen palm (Syagrus romanzoffiana) for the removal of 2,4-dichlorophenoxyacetic acid (2,4-D), the fruit of guapuruvu (Schizolobium parahyba) for the removal of atrazine, and the seeds of persimmon (Diospyros kaki) for the removal of ketoprofen. The adsorbents were named activated carbon from the endocarp of the queen palm (QPPAC), activated carbon from persimmon seeds (PSAC), and activated carbon from the fruit of guapuruvu (GFRAC). In general, the surfaces of the materials exhibited porosity and high surface area, favoring adsorption. The surface area values of the adsorbents were 782 m² g-1 (QPPAC), 1067 m² g-1 (PSAC), and 981 m² g-1 (GFRAC). For the QPPAC adsorbent, the optimal pH was found to be 2 with a dosage of 0.5 g L-1, achieving a removal efficiency of 95.4%. For the PSAC adsorbent, the optimal pH was 7.0 with a dosage of 0.43 g L-1, resulting in a 77% removal efficiency and an adsorption capacity of 91 mg g-1. In the case of GFRAC, the molecules adhered better to the adsorbent's surface under acidic conditions (pH = 2), resulting in an ideal dosage of 0.7 g L-1. The kinetic models that best fitted the data were the pseudo-second order model for QPPAC, the LDF model for PSAC, and the general order model for GFRAC. To describe the equilibrium data, the most suitable models were the Langmuir, Freundlich, and Tóth models for the adsorbents QPPAC, PSAC, and GFRAC, respectively. The maximum adsorption capacities were 367.77 mg g-1 for QPPAC, 211.5 mg g-1 for PSAC, and 229 mg g-1 for GFRAC. The thermodynamic studies indicated an endothermic process and spontaneous nature for the materials. Regeneration studies were conducted, and the adsorption capacity of QPPAC was maintained over 7 cycles. For the desorption study with GFRAC, the adsorption capacity increased until the 5th cycle and then decreased until no adsorption occurred after the 12th cycle. A study was also conducted to evaluate the performance of the PSAC adsorbent using a sample from the Jacuí River containing atrazine, yielding a removal efficiency of 85%. Finally, the treatment of simulated effluent with the GFRAC material showed an efficiency of 90% in removing effluent containing ketoprofen, ibuprofen, and salts. Thus, the activated carbons prepared from the adsorbents QPPAC, PSAC and GFRAC proved to be effective materials for the removal of herbicides and pharmaceutical products in wastewater.